Hegemonic Discourse dan Hegemonic Actor Potensi Konflik Sosial Menjelang Pemilihan Presiden - santoso, didik haryadi (Jurnal Pekommas, 2023)
This study aims to explore how hegemonic discourse is related to the potential for social conflict in virtual space ahead of the 2024 presidential election and find out how the hegemonic actors are involved. This research is a qualitative research analysis of Laclau & Mouffe's discourse with data collection methods through web crawlers and SNA. This study found that; First, the hegemonic discourse on the potential for social conflict ahead of the presidential election is divided into two, namely (1) the potential for SARA conflict and (2) the potential for political conflict. SARA conflict refers to the potential for ethnic and religious conflict. The potential for political conflict that occurs in virtual space is found in the three presidential candidates, namely Anies, Ganjar and Prabowo. Second, Hegemonic Actors in the discourse ahead of the presidential election are dominated by non-state actors or intellectual actors and buzzers who are connected to a network of fellow supporters, and not from state actors and online news. Apart from the Hegemonic Actor, the contestation of actors in the presidential election discourse is divided into four main actor clusters, namely the Anies Baswedan, Erick Thohir, Ganjar Pranowo, and online news clusters.